Evaluation of Mode I interlaminar fracture toughness in asymmetric interlayer in CFRP laminates. (3rd March 2020) - Saito, Hiroshi; Kikuchi, Ryosuke; Kimpara, Isao
Abstract : Assuming the interlaminar failure in quasi-isotropic laminates, we evaluated the Mode I interlaminar fracture in asymmetric 0°/45° interlayer. To consider coupling effects caused by stacking sequence, we prepared two types of laminates with 0°/45° interlayer: one is that all coupling components are zero, and the other has non-zero D 16 and D 26 components. As for comparisons, we used unidirectional laminates and angle-ply laminates in which the midplane consisted of a ± 22.5° interlaminar. The laminates with the 0°/45° or ±22.5° interlayers exhibited higher energy release rates than that of the 0°/0° laminates, owing to significant bridging fibers. It was experimentally confirmed that a failure in asymmetric interlayer, which has non-zero coupling components like typical quasi-isotropic laminates, did not propagate straight along a fiber direction on either side, but was distorted in fan-like shape by coupling effects.